Local Wisdom Equality in Marriage of Gold Entrepreneurs in Kasui Pasar Village - Jayusman Jayusman; Efrinaldi Efrinaldi; Shafra Shafra (Jurnal Ilmiah Al-Syir'ah, 2023)
This article aims to elaborate on equivalence in marriage. Equivalence is one of the essential aspects of creating a harmonious family. The people of Kasui Pasar Village, who are from Banten ethnic background, have a tradition of marital equivalence regarding profession and ethnicity. The problem in this study is how to review Islamic law on the tradition of marriage equivalence in realizing a harmonious family in Kasui Pasar Village. This type of research is field research descriptive-analytical. The primary data of this research are the results of interviews and observations with a married couple of Banten ethnic gold traders. Secondary data are books, journals, and related research. Data collection techniques in this study are interviews, observation, and documentation. Then the data obtained is processed and analyzed inductively using urf theory. The results of this study indicate that the community believes that marriage equivalence in the profession of gold business people and ethnic Banten is the main factor in the realization of a harmonious family. This local wisdom as urf sahih has brought benefits and goodness in their lives and is inherent and accepted by the general public, especially in Kasui Pasar Village. This tradition does not conflict with Islamic law. The results of this study indicate that the community believes that marriage equivalence in the profession of gold traders and ethnic Banten is the main factor in the realization of a harmonious family. This local wisdom as urf sahih has brought benefits and goodness in their lives and is inherent and accepted by the general public, especially in Kasui Pasar Village. This tradition does not conflict with Islamic law.